The Effect of Chief Executive Officer and Board Prior Corporate Social Responsibility Experiences on Their Focal Firm’s Corporate Social Responsibility: The Moderating Effect of Chief Executive Officer Overconfidence - Al-Shammari, Marwan; Al-Shammari, Hussam; Banerjee, Soumendra Nath; Doty, D. Harold (Frontiers in Psychology, 2022)
We examine how the prior experiences of the chief executive officer (CEO) and board influence the focal firm’s Corporate Social Responsibility (CSR) activities. Further, we examine how CEO overconfidence influences the diffusion of CSR activities. We theorize that overconfident CEOs are influenced more by the corporate strategies they experienced on other boards and less by the corporate strategies experienced by other directors. Through longitudinal analyses of the CSR profiles a sample of S&P 500 companies for the period 2006-2013, we show that CEO and board prior CSR experience are positively related to the firm’s current CSR activities. We find a significant positive moderating effect of CEO overconfidence on the relationship between CEO prior CSR and the focal firm’s CSR. Our theory and results highlight how CEO and board prior CSR exposure may influence the focal firm’s stances towards CSR and that CEO overconfidence may have differential effects on these relationships.